2019
DOI: 10.1111/aos.14242
|View full text |Cite
|
Sign up to set email alerts
|

Low physical activity and higher use of screen devices are associated with myopia at the age of 16‐17 years in the CCC2000 Eye Study

Abstract: Purpose: To determine the myopia prevalence in a Danish cohort aged 16-17 years and its relation to physical activity and use of screen-based electronic devices. Methods: The Copenhagen Child Cohort 2000 Eye Study is a prospective, population-based, observational study. Information about use of screen devices and physical activity was obtained using questionnaires. Myopia was defined as non-cycloplegic subjective spherical equivalent refraction ≤À0.50 D in right eye. Results: We included 1443 participants (45%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 39 publications
1
87
1
5
Order By: Relevance
“…We identified 29 Danish studies reporting on prevalence of myopia including four Danish doctoral theses (Bjerrum 1884, Bjerrum 1913, Bjerrum & Philipsen 1883, Engbæk 1970, Engbæk 1982, Fledelius 1976, Fledelius 1983, Fledelius 2000, Fledelius & Stubgaard 1986, Goldschmidt 1968, Goldschmidt 1969, Goldschmidt 1966, Hansen et al 2020b, Holm 1925, Jacobsen et al 2007, Jacobsen et al 2008, Jensen 1899, Jensen 1991, Johansen 1950, Kessel et al 2004, Knudtzon 1941, Lebel 1957, Lundberg et al 2018, Lundsgaard 1927, Øster & Kjærgaard 1964, Sandfeld et al 2019, Teasdale & Goldschmidt 1988, Tscherning 1882, X. Li 2012 unpublished). The earliest study was published in 1882 (Tscherning 1882) and the latest in 2018 (Sandfeld et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 29 Danish studies reporting on prevalence of myopia including four Danish doctoral theses (Bjerrum 1884, Bjerrum 1913, Bjerrum & Philipsen 1883, Engbæk 1970, Engbæk 1982, Fledelius 1976, Fledelius 1983, Fledelius 2000, Fledelius & Stubgaard 1986, Goldschmidt 1968, Goldschmidt 1969, Goldschmidt 1966, Hansen et al 2020b, Holm 1925, Jacobsen et al 2007, Jacobsen et al 2008, Jensen 1899, Jensen 1991, Johansen 1950, Kessel et al 2004, Knudtzon 1941, Lebel 1957, Lundberg et al 2018, Lundsgaard 1927, Øster & Kjærgaard 1964, Sandfeld et al 2019, Teasdale & Goldschmidt 1988, Tscherning 1882, X. Li 2012 unpublished). The earliest study was published in 1882 (Tscherning 1882) and the latest in 2018 (Sandfeld et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…As we included historical reports different approaches were used to evaluate refraction. Four studies evaluated the refraction using an ophthalmoscope/retinoscope (Tscherning 1882; Bjerrum & Philipsen 1883; Bjerrum 1884; Goldschmidt 1969), seven used subjective spherical equivalent refraction (Fledelius 1976; Fledelius 1983; Fledelius & Stubgaard 1986; Kessel et al 2004; Jacobsen et al 2007; Hansen et al 2020b, X. Li 2012 unpublished), three used the spherical equivalent refraction measured with an automated refractometer (Jacobsen et al 2008; Lundberg et al 2018; Sandfeld et al 2019), nine used the subjective spherical refraction (Jensen 1899; Bjerrum 1913; Holm 1925; Lundsgaard 1927; Johansen 1950; Lebel 1957; Goldschmidt 1968; Teasdale & Goldschmidt 1988; Goldschmidt 1966), one used self‐reported spherical equivalent refraction (Fledelius 2000), and five did not elaborate on their method of examination (Knudtzon 1941; Øster & Kjærgaard 1964; Engbæk 1970; Engbæk 1982; Jensen 1991). The latter were all performed as part of school screening programs where noncycloplegic subjective spherical refraction is usually used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies concerning screen exposure and myopia have been conducted worldwide such as in China, Japan, India, Ireland and Denmark with a focus on school-age children, which led to discrepant findings. A study involving primary and middle school students in six provinces of China showed children had a higher risk of myopia whose parents did not limit their offspring's screen time [25]; Siofra and colleagues reported that using screens >3 h per day was associated with a higher risk of myopia among schoolchildren in Ireland [26]; the North India Myopia Study found screen viewing was a significant risk factor for myopia progression amongst children aged 5 to 15 years [10]; and the Copenhagen Child Cohort 2000 Eye Study revealed that using screen devices >6 h/day, compared to screen device use <2 h/day, induced a roughly doubled risk of having myopia among [16][17] year-old adolescents [27]. Moreover, another two studies in older children aged 6 to 18 years in Qatar demonstrated a highly positive association between prolonged screen time (more than 3 h/day) and poor vision [28,29].…”
Section: Discussionmentioning
confidence: 99%